Methods and means of expressing pragmatic meaning in conversation - Sattorova, Feruza (The Lingua Spectrum, 2025)
The effectiveness of communication depends primarily on accurately grasping the speaker’s intended content – its pragmatic meaning. While linguistic resources – lexical, grammatical, and syntactic – are central to encoding information, the intended sense often becomes fully visible through non-linguistic factors such as context, communicative setting, participants’ social roles, prosody, kinesics, and cultural scripts. Their alignment reveals not only what is said, but how and why it is said. Comprehending less overt layers – implicatures, presuppositions, and connotations – therefore requires a systematic study of the methods and means that shape pragmatic content. Building on this, analyses incorporate speech strategies and behavioral norms, politeness, staged cooperation, and the principle of relevance. As a result, potential misunderstandings in interaction are reduced, including cross-cultural semantic shifts, ambiguous cues, and misreadings of communicative intent. Consequently, developing pragmatic literacy is a priority in language education and yields durable outcomes across translation, media, and pedagogical practice.